Photosynthesis on habitable planets around low-mass stars. Issue 4 (27th March 2019) - Lingam, Manasvi; Loeb, Abraham
Abstract: We show that planets around M-dwarfs with M ⋆  ≲ 0.2 M⊙ may not receive enough photons in the photosynthetically active range of 400–750 nm to sustain Earth-like biospheres. As a result of the lower biological productivity, it is likely that biotic molecular oxygen would not build-up to detectable levels in the atmospheres of habitable planets orbiting low-mass stars, consistent with prior work by Lehmer et al. We also estimate the minimum flaring rate for sustaining biospheres with Earth-like productivity and permitting the build-up of atmospheric oxygen, and find that the overwhelming majority of M-dwarfs are unlikely to exceed this threshold.